A Phase 2, Single Arm Study of Iniparib in Patients With BRCA1 or BRCA2 Associated Advanced Epithelial Ovarian, Fallopian Tube, or Primary Peritoneal Cancer. Issue 2 (1st February 2016) - Bell-McGuinn, Katherine M.; Konner, Jason A.; Tew, William P.; Hensley, Martee L.; Iasonos, Alexia; Charpentier, Eric; Mironov, Svetlana; Sabbatini, Paul; Aghajanian, Carol
Abstract : Objective: The aim of the study was to evaluate the activity and tolerability of iniparib monotherapy in women with BRCA1 or BRCA2- associated advanced epithelial ovarian, fallopian tube, or primary peritoneal cancer. Methods and Materials: Eligible patients had advanced epithelial ovarian, fallopian tube, or primary peritoneal cancer, germline BRCA1 or BRCA2 mutation, measurable disease, and at least 1 previous treatment regimen of platinum/taxane chemotherapy. Patients received iniparib 8 mg/kg intravenously on days 1 and 4 weekly, with imaging every 8 weeks. Treatment continued until disease progression or adverse events (AEs) prohibited further therapy. Common Terminology Criteria for AEs v3.0 was used to grade AEs. The primary endpoint was tumor response. The study was conducted with a Simon 2-stage design with 12 and 23 patients planned in the first and second stage, respectively. The study was designed to distinguish between 10% and 30% responding with types 1 and 2 error of 0.10. Results: Twelve patients were treated on study, with median exposure to iniparib of 7.5 weeks. The median number of previous chemotherapeutic regimens was 7. Treatment-related AEs (≥10%) included asthenia (83.3%), constipation (25%), diarrhea (25%), nausea (25%), abdominal pain (16.7%), and decreased hemoglobin (16.7%). All treatment-related AEs were grades 1 or 2 with the following 2 exceptions: 1 grade 3 diarrhea and 1 grade 3 hypertension. One patient had stable disease lasting 2 cycles; the remaining 11 patients had progressive disease. The study did not proceed to second stage enrollment. Conclusions: Iniparib did not show significant activity in this heavily pretreated ovarian cancer population, all of whom had BRCA1 or BRCA2 mutations.